Does occupational exposure to formaldehyde cause hematotoxicity and leukemia-specific chromosome changes in cultured myeloid progenitor cells?. (9th August 2017) - Mundt, Kenneth A.; Gallagher, Alexa E.; Dell, Linda D.; Natelson, Ethan A.; Boffetta, Paolo; Gentry, P. Robinan
Abstract: Several cross-sectional studies of a single population of workers exposed to formaldehyde at one of two factories using or producing formaldehyde–melamine resins in China have concluded that formaldehyde exposure induces damage to hematopoietic cells that originate in the bone marrow. Moreover, the investigators interpret observed differences between groups as evidence that formaldehyde induces myeloid leukemias, although the mechanisms for inducing these diseases are not obvious and recently published scientific findings do not support causation. Our objective was to evaluate hematological parameters and aneuploidy in relation to quantitative exposure measures of formaldehyde. We obtained the study data for the original study (Zhang et al.2010 ) and performed linear regression analyses. Results showed that differences in white blood cell, granulocyte, platelet, and red blood cell counts are not exposure dependent. Among formaldehyde-exposed workers, no association was observed between individual average formaldehyde exposure estimates and frequency of aneuploidy, suggested by the original study authors to be indicators of myeloid leukemia risk.